2008
DOI: 10.1002/mnfr.200700329
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin, a bioactive flavonoid in herbal tea, inhibits inflammatory cyclooxygenase‐2 gene expression in human lung epithelial cancer cells

Abstract: Wogonin, a naturally occurring plant flavonoid, is isolated from Chinese herbal plants Scutellaria baicalensis Georgi and S. barbata D. Don. The extract of S. baicalensis Georgi has been added to an assortment of health drinks or food supplements. Wogonin has been reported to exhibit anticancer and anti-inflammatory properties. Cyclooxygenase-2 (COX-2) is a key enzyme in the production of prostaglandins in inflammatory conditions. In this study, the effect of wogonin on phorbol 12-myristate 13-acetate (PMA)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 36 publications
3
34
0
1
Order By: Relevance
“…Furthermore, ZMYL could reverse CDDPresistance of resistant ovarian cancer in nude mice and enhance the tumor inhibitory effect Qi et al, 2012). In addition, several components in ZMYL, such as paeoniflorin, albiflorin, and wogonin, have been reported to have antitumor activity or to enhance the efficacy of CDDP radiation and chemotherapy as well as oppose the toxicity of chemotherapy-induced myelosuppression (Chen et al, 2008;Xu et al, 2011;Yu et al, 2007). These results indicate that ZMYL is a potential complementary and alternative medicine during CDDP chemotherapy.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, ZMYL could reverse CDDPresistance of resistant ovarian cancer in nude mice and enhance the tumor inhibitory effect Qi et al, 2012). In addition, several components in ZMYL, such as paeoniflorin, albiflorin, and wogonin, have been reported to have antitumor activity or to enhance the efficacy of CDDP radiation and chemotherapy as well as oppose the toxicity of chemotherapy-induced myelosuppression (Chen et al, 2008;Xu et al, 2011;Yu et al, 2007). These results indicate that ZMYL is a potential complementary and alternative medicine during CDDP chemotherapy.…”
Section: Introductionmentioning
confidence: 94%
“…En la tabla 2 se presenta un resumen de los principales estudios realizados en modelos celulares y animales al respecto 51,52,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] . Un estudio in vivo con ratones a los que se induce cáncer mediante la molécula benzo(a)pireno, presente en el humo del tabaco, muestra la capacidad de la fisetina, un flavonol presente en frutas y hortalizas (fresa, manzana, caqui, uva, cebolla y pepino), para inhibir la proliferación celular y el desarrollo de tumores, gracias a sus propiedades antioxidantes 68 .…”
Section: Flavonoides Y Cáncer De Pulmónunclassified
“…It has been reported that S. baicalensis and S. barbata have diverse biological activities that are anti-inflammatory [9], antioxidative [9], and antibacterial [10]. Recent investigations show that S. baicalensis and S. barbata alone, or in combination with other herbs, can inhibit cancer cell proliferation or induce apoptosis in breast [11], hepatocellular [12], lung [13], prostate [14], colon [15], and gynecologic neoplasms [16]. However, it is still unclear whether these activities are caused by the additive or synergistic effects of several components of S. baicalensis or S. barbata, or due to a single component of them.…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin induces apoptosis of Lewis lung carcinoma cells by effectively activating caspase 9 and 3 and down-regulating the expression of extracellular signal-regulated kinase (ERK) and Akt [22]. Wogonin can inhibit phorbol 12-myristate 13-acetate-induced COX-2 gene expression in human lung epithelial cancer A549 cells [13] and promote the granulocytic differentiation of human promyelocytic leukemia cells by upregulating the expression of phospholipid scramblase 1 gene [23]. Scutellarein, 5,6,7,4'-Tetrahydroxy flavone, is a flavonoid monomer composition of S. baicalensis and S. barbata.…”
Section: Introductionmentioning
confidence: 99%